FTIR spectroscopy for the detection and evaluation of live attenuated viruses in freeze dried vaccine formulations. (4th June 2015) - Hansen, Laurent; De Beer, Thomas; Pierre, Karin; Pastoret, Soumya; Bonnegarde‐Bernard, Astrid; Daoussi, Rim; Vervaet, Chris; Remon, Jean Paul
<x xml:space="preserve">Abstract</x> This article examines the applicability of Fourier Transform Infrared (FTIR) spectroscopy to detect the applied virus medium volume (i.e., during sample filling), to evaluate the virus state and to distinguish between different vaccine doses in a freeze dried live, attenuated vaccine formulation. Therefore, different formulations were freeze dried after preparing them with different virus medium volumes (i.e., 30, 100, and 400 µl) or after applying different pre‐freeze‐drying sample treatments (resulting in different virus states); i.e., (i) as done for the commercial formulation; (ii) samples without virus medium (placebo); (iii) samples with virus medium but free from antigen; (iv) concentrated samples obtained via a centrifugal filter device; and (v) samples stressed by 96h exposure to room temperature; or by using different doses (placebo, 25‐dose vials, 50‐dose‐vials and 125‐dose vials). Each freeze‐dried product was measured directly after freeze‐drying with FTIR spectroscopy. The collected spectra were analyzed using principal component analysis (PCA) and evaluated at three spectral regions, which might provide information on the coated proteins of freeze dried live, attenuated viruses: (i) 1700–1600 cm−1 (amide I band), 1600–1500 cm−1 (amide II band) and 1200–1350 cm−1 (amide III band). The latter spectral band does not overlap with water signals and is hence not influenced by residual moisture in the samples. It was proven that FTIR could distinguish between the freeze‐dried samples prepared using different virus medium volumes, containing different doses and using different pre‐freeze‐drying sample treatments in the amide III region. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1107–1118, 2015